2012
DOI: 10.1097/shk.0b013e3182596ec4
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Crocetin on Hemorrhagic Shock–Induced Acute Renal Failure in Rats

Abstract: Multiple organ failure is a common outcome of hemorrhagic shock followed by resuscitation, and the kidney is one of the prime target organs involved. The main objective of the study was to evaluate whether crocetin, a natural product from Gardenia jasminoides Ellis, has beneficial effects on renal dysfunction caused by hemorrhagic shock and resuscitation in rats. Anesthetized rats were bled to reduce mean arterial blood pressure to 35 (SD, 5) mmHg for 60 min and then were resuscitated with their withdrawn shed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 29 publications
0
31
0
1
Order By: Relevance
“…This inhibition was associated with reduced cell proliferation through the downregulation or upregulation of certain apoptotic proteins, including cytochrome c and cleaved caspase-3 expression. In addition, a number of pharmacological studies have demonstrated crocetin to have multiple activities, including anti-inflammatory (35,36) and anti-oxidant (37,38) effects. Therefore, it was hypothesized that the anti-oxidant and anti-inflammatory effects of crocetin may also be considered to be involved in several synergistic antitumor mechanisms (39,40).…”
Section: D a Bmentioning
confidence: 99%
“…This inhibition was associated with reduced cell proliferation through the downregulation or upregulation of certain apoptotic proteins, including cytochrome c and cleaved caspase-3 expression. In addition, a number of pharmacological studies have demonstrated crocetin to have multiple activities, including anti-inflammatory (35,36) and anti-oxidant (37,38) effects. Therefore, it was hypothesized that the anti-oxidant and anti-inflammatory effects of crocetin may also be considered to be involved in several synergistic antitumor mechanisms (39,40).…”
Section: D a Bmentioning
confidence: 99%
“…Moreover, despite consistent methods, the creatinine levels were not always increased to the same degree by the injury [73], highlighting the substantial challenge of variability in animal models of AKI that inherently comes with in vivo studies. A similar study performed by Wang et al demonstrated that the increased MDA levels after HS in rats was reduced by treatment with the antioxidant crocetin [58]. These researchers concluded that although HS reduced total SOD, crocetin provided protection by elevating total SOD.…”
Section: Accepted Manuscriptmentioning
confidence: 81%
“…iNOS and NO production are also generated during hypoxia in rat proximal tubules [58,61] . NO derived from iNOS propagates the inflammatory response and contributes to enhanced tissue damage.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Пошкодження клітин нирки викликає ішемію тканин, яка ініціює складний і взаємопов'я-заний ланцюг подій, а оксид азоту відіграє вирі-шальну роль в нирковій функції і може інгібуватись аміногуанідіном (AГ) [3,7,16].…”
unclassified